The Influence of Role Clarity and Communication Quality on Organizational Performance through Job Satisfaction in MSMEs in Medan City - Albert Albert; Janssen Yohana Putri Hartanto; James Hwang; Jovan Mulyono; Tierlin Gustin Kristiani Laoli (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of Role Clarity and Communication Quality on Organizational Performance with Job Satisfaction as a mediating variable in MSMEs in Medan City. Field phenomena indicate that most MSMEs still face problems related to unclear tasks, ineffective communication flows, and low job satisfaction that impact performance achievement. This study uses a quantitative approach with a survey method on 155 MSME respondents. Data analysis was conducted using Structural Equation Modeling (SEM-PLS) to test the direct and indirect relationships between variables. The results show that Role Clarity and Communication Quality have a positive and significant effect on Job Satisfaction. In addition, Job Satisfaction significantly affects Organizational Performance. Both independent variables also have a direct effect on Organizational Performance, but the indirect effect through Job Satisfaction shows a stronger contribution. These findings confirm that psychological aspects and work relationships play an important role in improving MSME performance. Practically, this study provides recommendations for MSMEs to strengthen role clarity, improve communication quality, and prioritize job satisfaction to encourage improved organizational performance. Theoretically, the research findings support and expand the study of organizational behavior in the context of MSMEs.